Traffic Noise Levels and Hearing Impairment Among Shop Keepers in a Metropolitan City – An Embedded Mixed-Method Study - Kirubakaran S; Manoj Kumar K; Arun Murugan (National Journal of Community Medicine, 2025)
Context: Traffic noise and its impact on shop keepers is studied less. Use of mobile application for assessing noise levels and hearing impairment might provide solution in resource poor settings. Aims: Assess hearing impairment in shop keepers of traffic busy roads. Measure the noise exposure and monitor the community noise level in that locality. Find association between noise exposure and level of hearing impairment.